Microstructure Analysis of Glass/Epoxy Structure Reinforced with Multi- Walled Carbon Nanotubes - Vivek Balachandran; Sandeep Gupta (International Journal of Engineering and Management Research, 2018)
This work involves extensive experimental work to analyses the natural frequency of glass/epoxy honeycomb structures reinforced with 0 %, 0.5 %, 1 % and 1.5 % respectively which are prepared by hand layup method followed by vacuum bagging technique. An experimental investigation is carried out using modal analysis technique, to obtain the natural frequencies and the results show significance influence of the carbon nano tube on the natural frequency. Further microstructure analysis were also performed to analyze the surface integrity and dispersion of multi-walled carbon nano tubes in glass/epoxy composites.